Expression of Kisspeptin 1 in the Brain of the Adult Sea Lamprey Petromyzon marinus - Daniel Sobrido-Cameán; Luis Alfonso Yáñez-Guerra; Alexandre Deber; María Celina Rodicio; Antón Barreiro-Iglesias (Life, 2021)
Kisspeptin peptides play major roles in the regulation of reproduction and puberty onset in mammals. While most mammals only have one kisspeptin gene, other jawed vertebrates present two or three genes. Recent data also revealed the presence of two genes in lampreys (jawless vertebrates). However, apart from gene sequence data, there is almost no information on the kisspeptinergic system of lampreys. Here, we report phylogenetic and cluster-based analyses showing that the duplication of the ancestral kisspeptin gene occurred before the separation of jawless and jawed vertebrates. We also studied the expression of the kisspeptin transcripts in the brain of post-metamorphic juveniles and upstream migrating adult sea lampreys. Our in situ hybridization results revealed expression of kisspeptin 1 in hypothalamic neurons, which indicates that the hypothalamic expression of kisspeptins is an ancestral character in vertebrates. We also observed the presence of kisspeptin 1 expressing neurons in the paratubercular (posterior tubercle) nucleus of the diencephalon. This is the first description of the presence of kisspeptin 1 expressing neurons in this brain region in any vertebrate. We did not detect expression of kisspeptin 2 in the juvenile or adult sea lamprey brain with in situ hybridization. Our data provides an anatomical basis to study the role of kisspeptin 1 in the hypothalamic-pituitary system of lampreys and the contribution of diencephalic kisspeptinergic neurons to different circuits of the lamprey brain.